Enteral but not parenteral antibiotics enhance gut function and prevent necrotizing enterocolitis in formula-fed newborn preterm pigs - Birck, Malene M.; Duc Ninh, Nguyen; Cilieborg, Malene S.; Shamrulazhar, Shamzir Kamal; Nielsen, Dennis Sandris; Damborg, Peter; Olsen, John E.; Lauridsen, Charlotte; Sangild, Per Torp; Thymann, Thomas (The American Physiological Society, 2015)
Pre-term infants are susceptible to infection and necrotizing enterocolitis (NEC) and are often treated with antibiotics. Simultaneous administration of enteral and parenteral antibiotics during the first days after preterm birth prevents formula-induced NEC lesions in pigs, but it is unknown which administration route is most effective. We hypothesized that only enteral antibiotics suppress gut bacterial colonization and NEC progression in formula-fed preterm pigs. Cesarean-delivered preterm pigs (90 –92% of gestation) were fed increasing amounts of infant formula from birth to day 5 and given saline (CON) or antibiotics (ampicillin, gentamicin, and metronidazole) via the enteral (ENT) or parenteral (PAR) route (n 16 –17). NEC lesions, intestinal morphology, function, microbiology, and inflammatory mediators were evaluated. NEC lesions were completely prevented in ENT pigs,whereas there were high incidences of mild NEC lesions (59 – 63%) in CON and PAR pigs (P 0.001). ENT pigs had elevated intestinal weight, villus height/crypt depth ratio, and goblet cell density and reduced gut permeability, mucosal adherence of bacteria, IL-8 levels, colonic lactic acid levels, and density of Gram-positive bacteria, relative to CON pigs (P 0.05). Values in PAR pigs were intermediate with few affected parameters (reduced lactic acid levels and density and adherence of Gram-positive bacteria, relative to CON pigs, P 0.05). There was no evidence of increased antimicrobial resistance following the treatments. We conclude that enteral, but not parenteral, administration of antibiotics reduces gut bacterial colonization, inflammation, and NEC lesions in newborn, formula-fed preterm pigs. Delayed colonization may support intestinal structure, function, and immunity in the immediate postnatal period of formulafed preterm neonates.